1999
DOI: 10.2172/756919
|View full text |Cite
|
Sign up to set email alerts
|

C-tank transfers: Transuranic sludge removal from the C-1, C-2, and W-23 waste storage tanks at Oak Ridge National Laboratory, Oak Ridge, Tennessee

Abstract: The organization chart at the end of these acknowledgments illustrates the project interfaces. The leadership and goal setting of G. L. Riner, DOE Transuranic Waste Program Manager, is acknowledged as a key success factor. He recognized the value of this technology and negotiated the critical agreement with DOE-HQ and AEAT to deploy the fluidic pulsed jet mixing system through the International Agreement. Throughout the project he set challenging goals for the team which required all of the project participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Mahoney et al (1994) and Eyler and Mahoney (1995) modeled mobilization and mixing in the horizontal storage tanks. Dahl et al (1999) investigated transfers from the C Tanks. Youngblood et al (1991) investigated transport of radioactive sludges at ORNL.…”
Section: Oak Ridge Studiesmentioning
confidence: 99%
“…Mahoney et al (1994) and Eyler and Mahoney (1995) modeled mobilization and mixing in the horizontal storage tanks. Dahl et al (1999) investigated transfers from the C Tanks. Youngblood et al (1991) investigated transport of radioactive sludges at ORNL.…”
Section: Oak Ridge Studiesmentioning
confidence: 99%
“…Symptoms of celiac disease include abdominal pain, gas, bloating, chronic diarrhea, constipation, oily stools, and an increased appetite that is associated with a change in weight (either weight loss or weight gain) (Collin et al, 2002;Dahl 2000). Gluten describes a group of proteins found in all forms of wheat and related grains, rye, barley, and tritcale.…”
Section: Chronic Gi Disordersmentioning
confidence: 99%
“…Murray and Peters (1999) reported that the campaign to retrieve waste from Tanks C-1 and C-2 was to be initiated in early 1999. Dahl et al (1999) described the results from these transfers. Tank C-2 was emptied first.…”
Section: Off-gas Skidmentioning
confidence: 99%